An Intertribal Business Court. (30th March 2023) - Crepelle, Adam
Abstract : Few Indian reservations have any semblance of a private sector. Consequently, poverty and unemployment are major problems in much of Indian country. While there are many reasons why private enterprise is scarce in Indian country, one of the foremost reasons is businesses do not trust tribal courts. Businesses' distrust of tribal courts is not unique as outsiders often fear bias in foreign tribunals. Similarly, businesses are often concerned about a court's capacity to adjudicate complex disputes. Federal diversity jurisdiction was developed to allay fear of bias, and many states have developed business courts to address questions about court capacity. Tribes can overcome these issues by creating an intertribal business court (IBC). Tribes will be free to sculpt the IBC as they see fit. However, the IBC's intertribal nature will help reduce fears of bias, and an IBC's focus on business disputes will answer doubts about court capacity. An IBC will also make tribal law more accessible, further increasing confidence in this new tribunal. As businesses gain greater confidence in tribal legal institutions through the IBC, they will be more likely to operate in Indian country. Accordingly, the IBC could help to transform tribal economies.